2020
DOI: 10.6000/2292-2598.2020.08.02.21
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Adolescent's Emotion Regulation with Dialectical Behavior Therapy's Skill Training: The Applications across Borderline, Mild, and Moderate Intellectual Disability

Abstract: Intellectual disability (ID) is characterized by significant limitations in intellectual and adaptive functioning emerging before the age of eighteen-years-old. Known as a pervasive developmental disorder, the disability disturbs the individual's functioning on a wide range of cognitive and social realms, which further result in failure at school and interpersonal relationships. Nonetheless, the capacity for emotion regulation (ER) serves as a key role in supporting the individual's adaptation despite having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…Although little research has tested the efficacy of specific training in emotional competencies, it has been shown that they can lead to significant benefits and improvements [33] for children [34], adolescents [35][36][37], and adults [38][39][40]. These programs tested different components, ranging from emotional recognition [34], emotional expression, emotional intelligence, and social-emotional learning by using heterogeneous techniques, such as discrete trial training methodology, computer-assisted procedures, dialectical behavior therapy, and drama therapy.…”
Section: Emotions and Intellectual Disabilitymentioning
confidence: 99%
“…Although little research has tested the efficacy of specific training in emotional competencies, it has been shown that they can lead to significant benefits and improvements [33] for children [34], adolescents [35][36][37], and adults [38][39][40]. These programs tested different components, ranging from emotional recognition [34], emotional expression, emotional intelligence, and social-emotional learning by using heterogeneous techniques, such as discrete trial training methodology, computer-assisted procedures, dialectical behavior therapy, and drama therapy.…”
Section: Emotions and Intellectual Disabilitymentioning
confidence: 99%